Putative Microbial Population Shifts Attributable to Nasal Administration of Streptococcus salivarius 24SMBc and Streptococcus oralis 89a - De Grandi, Roberta (Probiotics Antimicrob Proteins, 2018)
Changes in bacterial composition of nasal microbiota may alter the host’s susceptibility to several infectious and allergic diseases such as chronic rhinosinusitis and allergic rhinitis. The aim of this study was to evaluate the effects of 1-week administration of a probiotic product, composed by a combination of Streptococcus salivarius 24SMBc and Streptococcus oralis 89a, on the nostril microbiota. Differences in the nasal microbiota composition were investigated by using a next-generation sequencing approach. A strong and significant decrease in Staphylococcus aureus abundance was detected immediately after the bacterial administration. Moreover, comparing the microbial networks of nostril microbiota before and 1 month after the end of treatment, we detected an increase in the total number of both bacterial nodes and microbial correlations, with particular regard to the beneficial ones. Furthermore, a less abundance of microbial genera commonly associated to potential harmful bacteria has been observed. These results suggest a potential ability of S. salivarius 24SMBc and S. oralis 89a to regulate and reorganize the nasal microbiota composition, possibly favoring those microorganisms that may be able to limit the overgrowth of potential pathogens.